Tree species community spatial partition in function of soil drainage in an Araucaria forest fragment in Southern Brazil Partição espacial de espécies arbóreas em função da drenagem do solo em um fragmento de floresta com Araucária no Sul do Brazil - de Aguiar M.D.* (2014)
The relationship vegetation-soil can contribute to understand the forest structure, supporting biodiversity conservation. Thus, the aim of the present study was to verify the existence of spatial partition of the tree species community in an Araucaria forest fragment in function of soil drainage. For this sake, an environmental characterization (soil drainage, physical and chemical soil properties, topography, compression of soil, depth of soil and canopy cover) was realized in 25 plots of 20 × 20m, where tree individuals, with circumference at breast height ≥15.7 cm were previously counted, measured and identified. The data were analyzed by Mann-Withney test, non-parametric multivariate ANOVA (NPMANOVA), multivariate analysis (NMDS) and indicator species analysis. In this small spatial scale there were two drainage classes, corresponding to well and moderately-drained soils, with environmental differences that determined the richness, the spatial partition of the tree community and the occurrence of indicator species. Thus, we conclude that in the study forest fragment soil drainage spatial variations were determinant in the foristic-structural heterogeneity observed in tree community.